Peranan Sistem Agribisnis terhadap Keberhasilan Tumpangsari Cabai-Tembakau (Kasus Subak Di Desa Sukawati, Kecamatan Sukawati, Kabupaten Gianyar) - Adnyana, Surata; Tenaya, I Made Narke; Darmawan, Dwi Putra (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management); Vol 5 No 1 (2017): MEI 2017DO - 10.24843/JMA.2017.v05.i01.p06, 2017)
ABSTRACT The Role of System Agribusiness On Intercropping Success Of Chili-Tobacco (Subak Case in Sukawati Village, Sukawati Sub-District, Gianyar District) Agricultural development in Indonesia is still the mainstay and the most important sectors of the overall economy. One of the way, developing the potential of regions that still exist through horticulture and folk plantation and implement the correct agribusiness management system. Agribusiness as a sector of the folk economy still have bright prospects for further development, both to reinforce the folk's economy as well as Indonesia state devisa. Sukawati village very potential to develop the chili-tobacco intercropping system because it has the most suitable land and widest in Gianyar district. Chilitobacco plants have the same genus, can grow well, have local varieties that still exist, tobacco be grown are tobacco of the folk plantations who are used to the fringe. The study was conducted in the Sukawati Village that be selected purposively. The study population was all the farmers who have applied intercropping farming system of chilli-tobacco in 2013 and 2014 in 13 Subak in the Sukawati Village. The research sample amount 90 respondents were selected by simple random sampling method. The data were analyzed using quantitative descriptive method and relationship analysis with the partial least square (PLS) with help Smart PLS program. The analysis showed that are: (1) sub-systems procurement and distribution of production facilities contribute positive and significant toward the intercropping success of chilli-tobacco with good category; (2) sub-systems of farming contribute positive and significant toward the intercropping success of chilli-tobacco with good category; (3) sub-system of post-harvest and processing advanced contribute positive and significant toward the intercropping success of chilli-tobacco with good category; (4) sub-system marketing contribute positive and significant to the intercropping success of chilli-tobacco with less good category; and (5) sub-system supporting services contribute positive and significant toward the intercropping success of chillitobacco with good category. Suggestions can be submitted are: (1) informal education of farmers in the form of field schools and training should be improved; (2) the farmer groups that have formed a cooperative to business of production facilities only fertilizers need to cooperate with village government to form village-owned enterprises (BUMDES) in order to able to market the chilli-tobacco so that price stability can be maintained; and (3) other studies with the model and different variables need to be done further. Key words: role, agribusiness system, intercropping success